2007
DOI: 10.1007/s00464-007-9643-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of pancreatitis following endoscopically placed large-bore plastic biliary stents with and without biliary sphincterotomy for management of postoperative bile leaks

Abstract: Although not statistically significant, there is a higher rate of post-ERCP pancreatitis after placement of large-bore biliary stents when sphincterotomy is not performed. The additional complications of biliary sphincterotomy did not offset the reduction in post-ERCP pancreatitis. When large-bore biliary stents are used in the treatment of bile leak, a biliary sphincterotomy may avoid pancreatitis. Randomized trials are needed to determine whether there is a significant difference in overall complication rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 20 publications
0
58
0
4
Order By: Relevance
“…Simmons et al [25] reported a higher rate of post-ERCP pancreatitis after placement of large-bore biliary stents wihout EST than with EST. In contrast, recent reports concluded that EST was not effective for the prevention of post-ERCP pancreatitis and was not necessary for transpapillary stenting using SEMS [7,15,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Simmons et al [25] reported a higher rate of post-ERCP pancreatitis after placement of large-bore biliary stents wihout EST than with EST. In contrast, recent reports concluded that EST was not effective for the prevention of post-ERCP pancreatitis and was not necessary for transpapillary stenting using SEMS [7,15,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…36 In this study, the investigators identified a higher rate of post-ERCP pancreatitis after placement of large-bore biliary stents when sphincterotomy was not performed suggesting that sphincterotomy might be protective of post-ERCP pancreatitis when 10Fr stents are placed, and that otherwise sphincterotomy alone did not confer additional benefit for the treatment of bile leak. 36 Our findings confirm the results of a recent multicenter study of patients with post-cholecystectomy bile leaks. 37 In this study, 162 out of 178 patients (91%) had complete resolution of their bile leak after therapy with biliary sphincterotomy and biliary plastic stent placement.…”
Section: Discussionmentioning
confidence: 75%
“…Although biliary sphincterotomy does not add additional drainage, data from our institution shows a reduced rate of pancreatitis when large-bore plastic stents are placed for bile leaks when sphincterotomy is performed. 2 …”
Section: Discussionmentioning
confidence: 99%